Endovascular Repair for Kommerell’s Diverticulum and Right-Sided Aortic Arch - Kazuno, Kei (Ann Vasc Dis, 2017)
A 74-year-old man with hoarseness was diagnosed with a right-sided aortic arch and Kommerell’s diverticulum by computed tomography (CT). The diverticulum had a maximum diameter of 33 mm, and surgical intervention was chosen because of the possibility of rupture. A right common carotid to right subclavian artery bypass was constructed, stent-graft was placed after the branching of the right common carotid artery, and coil embolization of the diverticulum was performed via left brachial artery. No leaks were found on postoperative CT. Symptoms disappeared and the diverticulum became smaller soon after surgery. Thoracic endovascular aortic repair (TEVAR) for Kommerell’s diverticulum was safe and effective.